Seasoned equity offerings and customer–supplier relationships - Johnson, William C. (2019)
We investigate how seasoned equity offerings (SEOs) by issuers with large customers affect both trading partners’ market values and the relationship's health. We hypothesize that SEOs reveal adverse information about an issuer's major customers and find that issuers and their large customers experience negative returns on SEO announcements. These results are more pronounced when customers have higher levels of information asymmetry and when customer-supplier relationships are particularly important. Large customers of issuers experience larger declines in post-SEO sales, operating performance, and credit ratings than large customers of non-issuers. Also, SEO issuer sales to large customers and relationship duration significantly decline.